REPRESENTATION OF CAPITALISM IN THE MEDIA - Johnson, Otis (2018)
This research explores the relationship between the representation of capitalism in the media and its ability to maintain hegemony. Historical data on capitalism, its successes and failures are reviewed and combined with sociological theories to gain an understanding of how, and why capitalism, as an economic system, has remained dominant, and how the media has worked to maintain this.